2020
DOI: 10.1007/s12649-020-01234-8
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Biomass Fuel Properties for Rice Straw Pellets Using Torrefaction and Mixing with Wood Chips

Abstract: Utilization of rice pellets as biomass fuel has many challenges compared with wood pellets, including low heating value, low bulk density, and high ash content, that cause high logistic costs and clinker formation. To solve these problems, this study focused on upgrading the quality of rice straw pellets to improve logistic efficiency by torrefaction and mixing with wood chips. Torrefaction and mixing with wood chips was effective to improve the energy density, the mechanical durability and the contents of fix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Pellet production takes place by extrusion, which involves passing semi-dry biomass that has been previously processed into dust, sawdust, or shavings through a hole that is a few millimeters in size to create small cylinders that are cut to the necessary length and then cooled [ 27 , 28 ]. This procedure lowers the cost of handling, transport, and storage by increasing the bulk density of the biomass [ 29 , 30 , 31 ]. The statistics from FAOSTAT [ 32 ], which illustrate the rising level of pellet production globally ( Figure 1 ), highlight the significant importance of the pelletization process for energy production.…”
Section: Introductionmentioning
confidence: 99%
“…Pellet production takes place by extrusion, which involves passing semi-dry biomass that has been previously processed into dust, sawdust, or shavings through a hole that is a few millimeters in size to create small cylinders that are cut to the necessary length and then cooled [ 27 , 28 ]. This procedure lowers the cost of handling, transport, and storage by increasing the bulk density of the biomass [ 29 , 30 , 31 ]. The statistics from FAOSTAT [ 32 ], which illustrate the rising level of pellet production globally ( Figure 1 ), highlight the significant importance of the pelletization process for energy production.…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars have studied the co-torrefaction of biomass. For example, Kizuka [ 11 ] studied the fuel performance of rice straw pellets after the torrefaction of a mixture of rice straw and wood chips and found that when the reaction temperature was 250 °C and 50% wood chips were added, the calorific value of the mixed biochar increased from 16.09 MJ/kg to 16.8 MJ/kg and the energy density increased from 11.53 GJ/m³ to 12.04 GJ/m³ compared to that by the torrefaction of only rice straw; thus, the fuel utilization efficiency increased by using both wood chips and rice straw. Furthermore, Rodríguez [ 12 ] found that adding PP during vegetable waste torrefaction increased the calorific value and reduced the AC.…”
Section: Introductionmentioning
confidence: 99%
“…A new process was put forward as follows. The biomass is charred first and then ground to powder [4]. An increasing amount of attention is given to the preparation technology of this new biomass that can be used to form carbon fuel.…”
Section: Introductionmentioning
confidence: 99%